Copper Enhanced Monooxygenase Activity and FT-IR Spectroscopic Characterisation of Biotransformation Products in Trichloroethylene Degrading Bacterium: Stenotrophomonas maltophilia PM102. (8th September 2013) - Mukherjee, Piyali; Roy, Pranab
Abstract : Stenotrophomonas maltophilia PM102 (NCBI GenBank Acc. no. JQ797560) is capable of growth on trichloroethylene as the sole carbon source. In this paper, we report the purification and characterisation of oxygenase present in the PM102 isolate. Enzyme activity was found to be induced 10.3-fold in presence of 0.7 mM copper with a further increment to 14.96-fold in presence of 0.05 mM NADH. Optimum temperature for oxygenase activity was recorded at 36 ∘ C . The reported enzyme was found to have enhanced activity at pH 5 and pH 8, indicating presence of two isoforms. Maximum activity was seen on incubation with benzene compared to other substrates like TCE, chloroform, toluene, hexane, and petroleum benzene. K m and V max for benzene were 3.8 mM and 340 U/mg/min and those for TCE were 2.1 mM and 170 U/mg/min. The crude enzyme was partially purified by ammonium sulphate precipitation followed by dialysis. Zymogram analysis revealed two isoforms in the 70% purified enzyme fraction. The activity stain was more prominent when the native gel was incubated in benzene as substrate in comparison to TCE. Crude enzyme and purified enzyme fractions were assayed for TCE degradation by the Fujiwara test. TCE biotransformation products were analysed by FT-IR spectroscopy.